2008
DOI: 10.1783/147118908784734846
|View full text |Cite
|
Sign up to set email alerts
|

Integrating medical abortion into safe abortion services: experience from three pilot sites in South Africa

Abstract: Background and methodology South Africa's Choice on Termination of Pregnancy Act of 1996 provides for safe termination of pregnancy (TOP) in designated facilities in the public and private health sectors. In 2001, mifepristone-misoprostol medical abortion was approved for TOP up to 56 days, but this method is not yet available in the public sector. Information on the operational requirements for integrating mifepristone-misoprostol medical abortion into South Africa's public sector safe abortion services is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 23 publications
4
19
0
Order By: Relevance
“…This is consistent with findings in the literature, further enforcing the idea that medical abortion will be a positive contribution to women's sexual and reproductive health (Cooper et al, 2005;Kawonga et al, 2008). Medical abortion has the potential to not only save lives, but also to expand women's options for protecting their sexual and reproductive health.…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with findings in the literature, further enforcing the idea that medical abortion will be a positive contribution to women's sexual and reproductive health (Cooper et al, 2005;Kawonga et al, 2008). Medical abortion has the potential to not only save lives, but also to expand women's options for protecting their sexual and reproductive health.…”
Section: Discussionsupporting
confidence: 86%
“…For example, the acceptability of certain methods of abortion (Akin et al, 2009;Coyaji et al, 2001;Elul et al, 2001;Levine & Cameron, 2009;Teal, Harken, Sheeder, & Westhoff, 2009) or pain management regimens (Allen, Kumar, Fitzmaurice, Lifford, & Goldberg, 2006;Clark et al, 2002) has been well studied in recent years. Several situation analyses of abortion services and population-based surveys have also provided information on women's experiences with abortion services (Dickson et al, 2003;Duggal & Barge, 2003;Kawonga et al, 2008;Khan, Barge, Kumar, & Almroth, 1999;Lelong et al, 2005;Lie, Robson, & May, 2008). While the clinical acceptability and patient satisfaction literature provide some indication of the aspects of abortion care that women value once they arrive at a facility, they do not address the more fundamental question of what type of providers women prefer for pregnancy terminations.…”
mentioning
confidence: 99%
“…Earlier studies in South Africa have reported a high level of acceptance of use of misoprostol at home among both women 3 and providers. 4 In the USA, in an effort to simplify medical abortion provision and thus improve acceptability and access, the Planned Parenthood Federation of America recommended in 2005 that the in-clinic follow-up requirement be waived should it create undue hardship for women, if they could manage their follow-up with a serum hCG pregnancy test at a facility closer to them.…”
mentioning
confidence: 93%
“…1 Improving access to abortion services by introducing medical abortion at more primary care facilities is expected to address some of the existing barriers to safe abortion care in South Africa, in particular the shortage of providers willing to perform surgical abortions. [2][3][4] Current standard medical abortion care up to 63 days LMP in both the NGO and public sectors in South Africa involves oral mifepristone (200 mg) followed by misoprostol used 1-2 days later at home (800 mcg = 400 mcg sublingual and 400 mcg oral or buccal), and a follow-up visit at the abortion facility to assess completion of abortion.…”
mentioning
confidence: 99%